2003
DOI: 10.1079/bjn2003852
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipid modifications in elderly people after administration of two virgin olive oils of the same variety (Olea europaeavar.hojiblanca) with different triacylglycerol composition

Abstract: In the present study we examined whether two virgin olive oils (VOO1 and VOO2), of the same variety (Olea europaea var. hojiblanca) and with a similar composition of minor components but differing in the content of triacylglycerol molecular species, had different effects on blood pressure and plasma lipid levels in a healthy elderly population. Thirty-one participants, aged 84·9 (SD 6·4) years, were asked to participate in the study. No differences were found with regard to blood pressure after both experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Despite this fact, our results clearly show that the presence of MA in OO is quite active in determining gene expression changes in vivo, adding new evidence to previous findings of in vitro activity of this compound [13][14][15]20,21,37,38]. Independent of the mechanism involved, the present results reveal the additional effects of a minor component of EVOO with respect to the influence of OO and further support the idea that not all MUFAcontaining oils behave in the same way [5][6][7][8][9][10][11][12]. Two main categories of MUFA-containing oils can be found, those that are fruit juices (OO and avocado) and those coming from seed extraction (oleic acid-enriched safflower, oleic acidenriched sunflower and peanut oils).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Despite this fact, our results clearly show that the presence of MA in OO is quite active in determining gene expression changes in vivo, adding new evidence to previous findings of in vitro activity of this compound [13][14][15]20,21,37,38]. Independent of the mechanism involved, the present results reveal the additional effects of a minor component of EVOO with respect to the influence of OO and further support the idea that not all MUFAcontaining oils behave in the same way [5][6][7][8][9][10][11][12]. Two main categories of MUFA-containing oils can be found, those that are fruit juices (OO and avocado) and those coming from seed extraction (oleic acid-enriched safflower, oleic acidenriched sunflower and peanut oils).…”
Section: Discussionsupporting
confidence: 79%
“…OO, as a fruit juice, is a complex mixture where triglycerides (TGs) are combined with other biologically active substances, such as tocopherols, polyphenols and phytosterols, some of which have antioxidant and anti-inflammatory activities [2][3][4]. A whole panoply of experimental work had proven that these components might be responsible for the benefits of virgin OO [5][6][7]. Similar findings have also been described in animal studies dealing with the effects of OO on the vascular wall [8,9].…”
Section: Introductionmentioning
confidence: 61%
“…In contrast, the C to phospholipid ratio was raised significantly only in the erythrocyte membrane after the dietary OO. These data suggest that the differential effects of dietary OO are beyond the concentration of oleic acid [116] and may be influenced by triacylglycerol molecular species and the composition and amount of OO minor components [117].…”
Section: Hypertensionmentioning
confidence: 98%
“…It was reported that the differences between effects of different plant oils on blood lipid profiles may be related to their content of plant sterols [46-49]. Indeed, there has been renewed interest in the cholesterol lowering properties of speciality grains and unprocesses oils rich in plant sterols including amaranth oil [50,51], rice bran oil [52] (Berger et al, submitted), avocado oil [53], extra virgin olive oil [54], macadamian nut [55], and argan oil [56]. …”
Section: Physiological Effects Of Plant Sterolsmentioning
confidence: 99%